Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1167/iovs.11-8393
|View full text |Cite
|
Sign up to set email alerts
|

Flt23k Nanoparticles Offer Additive Benefit in Graft Survival and Anti-Angiogenic Effects When Combined with Triamcinolone

Abstract: Anti-VEGF nanoparticles (Flt23k) have a significant effect on decreasing neovascularization and lymphangiogenesis, resulting in increased graft survival in penetrating keratoplasty. This beneficial effect is synergistically enhanced with steroid treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…This result validated that albumin nanoparticles could prolong the expression of therapeutic plasmids. The effect of Flt23k in the form of poly L-lactideco-glycolide nanoparticles was tested by Cho et al 49 They performed this study in a murine cornea transplant model and found that subconjunctival injection of Flt23k poly L-lactideco-glycolide nanoparticle could reduce NV, lymphangiogenesis, and graft failure rate. In addition, combined Flt23k nanoparticle and steroid also elevated the 2-month graft survival rate significantly.…”
Section: Soluble or Modified Vegf Receptorsmentioning
confidence: 99%
“…This result validated that albumin nanoparticles could prolong the expression of therapeutic plasmids. The effect of Flt23k in the form of poly L-lactideco-glycolide nanoparticles was tested by Cho et al 49 They performed this study in a murine cornea transplant model and found that subconjunctival injection of Flt23k poly L-lactideco-glycolide nanoparticle could reduce NV, lymphangiogenesis, and graft failure rate. In addition, combined Flt23k nanoparticle and steroid also elevated the 2-month graft survival rate significantly.…”
Section: Soluble or Modified Vegf Receptorsmentioning
confidence: 99%
“…Growth Factor (VEGF) therapy, obtained both through corneal gene therapy and monoclonal antibody can significantly decrease corneal neovascularization and lymphangiogenesis, resulting in increased graft survival in keratoplasty [38].…”
Section: Iii)mentioning
confidence: 99%
“…194 In addition, a combination of Flt23k nanoparticles that deliver plasmids expressing anti-VEGF intrareceptor Flt23k and steroid treatment significantly reduces lymphangiogenesis and improves graft survival in a mouse model of corneal transplantation. 195 …”
Section: Diseases Associated With Corneal Lymphangiogenesismentioning
confidence: 99%